Consideration and validation of flight control requirements under all engine failure conditions for MEA. Issue 13 (12th April 2018) - Li, Xiyu; Xu, Shuhan; Bai, Zhiqiang
Abstract : Since the lower carbon emission and lower direct operating cost, MEA has drawn great attention worldwide. Considering and validating the flight control requirements under all engine failure conditions for MEA is the minimum design requirement, which is widely associated with aircraft characteristics, controllability and manoeuvrability, and system specialities such as electrical system, power plant system, hydraulic system, and avionics. Therefore, taking this topic as an example to illustrate a requirement validation process will be great interest to the aircraft design and integration, where the correctness and completeness of the requirements would be satisfied, the method and evidences of validation would be proposed, the requirement assumption validation and management should be presented, and scenario analysis and typical timeline analysis would be analysed. This paper presents the above processes from configuration, requirement definition and validation, to scenario analysis in compliance with SAE 4754A, which will be a fundamental process to the further verification and integration tasks.